2014
DOI: 10.1371/journal.pone.0111748
|View full text |Cite
|
Sign up to set email alerts
|

Stage-Specific Binding Profiles of Cohesin in Resting and Activated B Lymphocytes Suggest a Role for Cohesin in Immunoglobulin Class Switching and Maturation

Abstract: The immunoglobulin heavy chain locus (Igh) features higher-order chromosomal interactions to facilitate stage-specific assembly of the Ig molecule. Cohesin, a ring-like protein complex required for sister chromatid cohesion, shapes chromosome architecture and chromatin interactions important for transcriptional regulation and often acts together with CTCF. Cohesin is likely involved in B cell activation and Ig class switch recombination. Hence, binding profiles of cohesin in resting mature murine splenic B lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Genome-wide analysis identified 8118, 4766 and 10400 occupied regions for Separase, MCM2 and SMC1A respectively. The number of cohesin sites is consistent with previous published data ( 41 , 56 ), whereas to our knowledge, this is the first time that genome-wide distribution of MCM2 in asynchronous cells and Separase has been carried out. Furthermore, we found that during replication stress conditions induced by aphidicolin, cohesin and MCM2 regions were higher than under an unperturbed S-phase.…”
Section: Discussionsupporting
confidence: 92%
“…Genome-wide analysis identified 8118, 4766 and 10400 occupied regions for Separase, MCM2 and SMC1A respectively. The number of cohesin sites is consistent with previous published data ( 41 , 56 ), whereas to our knowledge, this is the first time that genome-wide distribution of MCM2 in asynchronous cells and Separase has been carried out. Furthermore, we found that during replication stress conditions induced by aphidicolin, cohesin and MCM2 regions were higher than under an unperturbed S-phase.…”
Section: Discussionsupporting
confidence: 92%
“…Genome-wide analysis of the sequenced tags defined 11860 occupied regions for SMC1A (P-value of 10−4 and FDR ≤ 0.05). In mammalian cells, cohesin-binding sites range widely from about 5,000 to more than 100,000 depending on cell type, antibody, and bioinformatic tools 19 20 40 41 . Their association with transcriptional elements was determined using the cis-regulatory element annotation system (CEAS).…”
Section: Resultsmentioning
confidence: 99%
“…Esco1 acetylates cohesin throughout interphase, even well before DNA replication is evident. As cohesin plays critical roles in formation or maintenance of interphase chromosome structure (2,3,14,15,(24)(25)(26)(27)(28)(29), one attractive model is that Esco1 contributes to these events, perhaps through impacts on chromosome loop formation or stabilization. In chromatin immunoprecipitation experiments, cohesin, Esco1, and the insulator protein CTCF all show significant colocalization at the bases of chromosome loops (3,5,14,15,29,30).…”
Section: Discussionmentioning
confidence: 99%